CREATION OF HUMAN RESOURCES IN THE FIELD OF SOCIAL MEDIA VIDEOGRAPHER TO SUPPORT THE PROMOTION OF AGRO- TOURISM PARK A THOUSAND FLOWERS IN RAYA VILLAGE, BERASTAGI SUB-DISTRICT, KARO DISTRICT - Sinulingga, Samerdanta; Meutia, Amalia; Br. Perangin-angin, Alemina (Journal of Community Research and Service, 2024)
This service aims to create qualified human resources in the field of social media videography to support the promotion of Taman Seribu Bunga Agrotourism in Raya Village, Berastagi District, Karo Regency. This service proposes a service method that involves intensive training and field practice for participants. The steps to be taken in this service include identification of the need to promote Taman Seribu Bunga Agrotourism through social media, detailed activity planning, development of comprehensive training materials, implementation of interactive and practical training, field practice at Taman Seribu Bunga Agrotourism, evaluation of participants and their work, and dissemination of results through social media. During the training, participants will gain knowledge about videography, shooting techniques, video editing, and marketing strategies through social media. They will also practice creating attractive and effective promotional videos for Taman Seribu Bunga Agrotourism. The result of this service will be an increase in participants' skills in the field of social media videography, which will help improve the promotion and attractiveness of Taman Seribu Bunga Agrotourism. The results of the participants' work will also be disseminated through social media to reach a wider audience. This activity aims to provide long-term benefits by creating competent human resources in the field of videography and marketing through social media, as well as increasing the promotional carrying capacity of Taman Seribu Bunga Agrotourism in Raya Village.